1997
DOI: 10.1103/physrevlett.79.313
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Instabilities in a Growing Yeast Colony: Experiment and Theory

Abstract: We study the growth of colonies of the yeast Pichia membranaefaciens on agarose film. The growth conditions are controlled in a setup where nutrients are supplied through an agarose film suspended over a solution of nutrients. As the thickness of the agarose film is varied, the morphology of the front of the colony changes. The growth of the front is modeled by coupling it to a diffusive field of inhibitory metabolites. Qualitative agreement with experiments suggests that such a coupling is responsible for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Recently, López and Jensen [36] introduced a class of models for the growth of colonial organisms, such as fungi and bacteria. The models are motivated by recent experiments [37] with the yeast Pichia membranaefaciens on solidified agarose film. Depending on the concentration of polluting metabolites, different front morphologies were observed.…”
Section: Models For Fungal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, López and Jensen [36] introduced a class of models for the growth of colonial organisms, such as fungi and bacteria. The models are motivated by recent experiments [37] with the yeast Pichia membranaefaciens on solidified agarose film. Depending on the concentration of polluting metabolites, different front morphologies were observed.…”
Section: Models For Fungal Growthmentioning
confidence: 99%
“…However, random sequential updates seem to be a more appropriate description of the experiments in Ref. [37], since realistic cells do not divide synchronously. Therefore it is still unclear to what extent the roughening transition of the model in Ref.…”
Section: Models For Fungal Growthmentioning
confidence: 99%
“…Agarose is agar that has been purified to remove agaropectin (a poorly defined, complex polysaccharide with sulfate or pyruvate side groups) (16). It has been used as a microbial substrate (19)(20)(21)(22) but is much more commonly used as a matrix for gel electrophoresis (23). Noble agar is a bleached and washed derivative of agar, resulting in a whiter gel (24), and is occasionally used as a growth substrate (25,26).…”
mentioning
confidence: 99%
“…These petals can potentially structure the colony by allowing it to concentrate growth to specific zones or form channels for nutrient excess and metabolite removal. A detailed analysis of this and more complex morphologies in giant yeast colonies has revealed that the likely determinants of the ultimate shape assumed include the nutrient and metabolite concentrations, the mechanical interaction with the underlying substratum, and potentially secreted ligands (Sams, 1997;A. Levchenko, unpublished results).…”
Section: From Cell Regulation Network To Cell -Cell Communication Nementioning
confidence: 99%